2013
DOI: 10.11607/jomi.3019
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Versus Zirconia Implants Supporting Maxillary Overdentures: Three-Dimensional Finite Element Analysis

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…Similar results were obtained by Çaglar et al in their analysis of finite element comparing zircon and titanium implants [33–35]. These results also correspond to the results of Osman et al who analyzed a denture model and, in comparing the two materials, found similar results but with smaller differences in the two materials [36], likely because the design of the prosthesis was different from the one studied here and from the designs in the previously cited studies.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained by Çaglar et al in their analysis of finite element comparing zircon and titanium implants [33–35]. These results also correspond to the results of Osman et al who analyzed a denture model and, in comparing the two materials, found similar results but with smaller differences in the two materials [36], likely because the design of the prosthesis was different from the one studied here and from the designs in the previously cited studies.…”
Section: Discussionsupporting
confidence: 90%
“…A recent finite element analysis comparing the stress/strain distribution between zirconia and titanium implants supporting maxillary overdentures revealed strain values of 2823 and 2497 με for zirconia and titanium implants, respectively (Osman et al. ). According to Wolf's mechanostat theory, both values were within the physiological remodeling range of the bone (Frost ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the importance of evaluating the patients' dexterity particularly when zirconia implants are employed for overdenture support cannot be overemphasized. Higher fracture incidence encountered in the zirconia group calls for further modifications of implant design to improve its biomechanical integrity (Osman et al 2013c).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from there being the esthetic issue due to gray color of titanium which becomes more prominent when the soft tissue condition is not optimal and it becoming visible through the mucosa [11] It may also cause a greyish discoloration of the peri-implant mucosa where as Ceramic abutments are reported to reduce soft tissue shadowing due to their color and enhanced translucency which may lead to optimal esthetic results in combination with all-ceramic crowns [18]. Plaque accumulation and bacterial colonization on titanium is also one of the bigger drawbacks [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Zirconiamentioning
confidence: 99%